Histopathological Study of the Freshwater Fish Ctenopharyngodon Idella Exposed to ?-Cyhalothrin 5% EC - G. Rajeswari.1 , Lalitha Vinnakota1 , V.Venkata Rathnamma2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Present study Lambda cyhalothrin is a synthetic pyrethroid widely used for pest management and public health applications to control insects. It is categorized as a restricted use pesticide in Extension Toxicology Network for its toxicity to fish. But its usage for the control of major pest in agriculture is being continued in developing countries like India. The freshwater fish Ctenopharyngodon idella were exposed in sub lethal concentrations (1/10 of lethal concentrations) of lambda cyhalothrin 5%EC for 1 and 12 days along with controls to study histopathological changes under light microscope in the selected tissues viz., liver, kidney and gill were examined. Swelling of the hepatocytes with diffuse necrosis and marked swelling of blood vessels were observed in the liver tissue. Tubules of the kidney were distended, with tubular cells of posterior kidney exhibiting marked necrotic changes. Pathology of the gill tissue showed shortened primary lamellae, loss of secondary lamellae and congestion of blood vessels and hyperplasia of branchial plates and the pathology increased with increasing exposure periods.